2022
DOI: 10.3389/fonc.2022.779175
|View full text |Cite
|
Sign up to set email alerts
|

Cell Division Cycle-Associated Genes Are Potential Immune Regulators in Nasopharyngeal Carcinoma

Abstract: BackgroundCell division cycle-associated (CDCA) gene family is essential to cell cycle regulation. Numerous studies have illuminated that dysfunction of CDCA genes may not only lead to uncontrolled cell proliferation resulting in tumorigenesis but also influence immune cell infiltration in tumors. However, the role of the CDCA gene family on the prognosis and immune infiltration in nasopharyngeal carcinoma (NPC) remains to be unclear.MethodsSBC human ceRNA array V1.0 was used to measure mRNA expression in thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 51 publications
(55 reference statements)
2
7
0
Order By: Relevance
“…High CDCA3 mRNA expression is substantially linked with several clinicopathologic characteristics in individuals with renal papillary kidney disease, according to Li et al High CDCA3 mRNA expression has been reported to be related to shorter overall survival, progression-free interval, and disease-specific survival (35). Similar results were discovered for malignancies of the lung, prostate, and nasopharynx (14)(15)(16). Overall, CDCA3 is an effective prognostic marker and a promising target for the development of novel anticancer therapies.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…High CDCA3 mRNA expression is substantially linked with several clinicopathologic characteristics in individuals with renal papillary kidney disease, according to Li et al High CDCA3 mRNA expression has been reported to be related to shorter overall survival, progression-free interval, and disease-specific survival (35). Similar results were discovered for malignancies of the lung, prostate, and nasopharynx (14)(15)(16). Overall, CDCA3 is an effective prognostic marker and a promising target for the development of novel anticancer therapies.…”
Section: Discussionsupporting
confidence: 73%
“…The cell cycle is regulated by a gene family related to cell division. Numerous studies have shown that CDCA gene malfunction can affect immune cell infiltration in tumors and unchecked cell proliferation that results in carcinogenesis ( 14 ). There has also been evidence of increased CDCA3 expression in many cancer types.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the fact that there was some inconsistency, chemotherapy response is connected with a multitude of parameters. The reason for this inconsistency could be owed to the presence of more basal/squamous-like subtypes in the GSE169455 dataset, which have been suggested to suppress chemotherapy efficacy [ 205 ], or to the CDCA8 ′s association with the immune cell infiltration, which could be a predictive biomarker for chemotherapy responsiveness [ 206 , 207 ]. Hence, there is growing evidence that CDCA8 may constitute an effective therapeutic target for prognosis and treatment of BCa, but its exact biological function remains still obscure and needs to be clarified.…”
Section: Discussionmentioning
confidence: 99%